Konformitas Internalisasi Siswa Terhadap Peraturan Sekolah dan Implikasinya dalam Layanan Bimbingan dan Konseling - Fatmi Yulfitri; Marjohan Marjohan; Afrizal Sano (Jurnal Konseling dan Pendidikan, 2014)
Internalization of conformity need to be developed in education. Development of internalization of conformity in school environment make students can optimize their internal ability to think, feel, consider everything in behaving to obey school rules. In fact the social causes make students adhere to school rules such as fear sanctioned, want to be praised. Shame ridiculed friends and others. This research aims to describe student’s internalization of conformity with the regulations of arrival and presence, rules in learning and common rules in school and their implications in guidance and counseling services. The method used is descriptive research. The instrument research is quistionnaire. The population in this research was all students MAN 1 Model Bukittinggi and samples are 90 people. The finding of the research revealed that  most of internalization of conformity student for rules relatively middle in schools relating to the regulation of arrival and presence, rules in learning and common rules in school.